Screening The Anticancer Activity for New Schiff Bases of Natural Steroids - Selman, Nawfal Abdul Samad; Abbas, Layla Jasim (Universitas Jenderal Soedirman, 2023)
The significance of cholesterol and ergosterol (provitamin d2) in biological systems has prompted interest in these compounds as pharmaceuticals. It has been reported on the effective straightforward synthesis of Schiff base modifications of cholesterol aldehyde and ergosterol aldehyde and their assessment as possible agents against cancer (esophagus natural cell lines and human cancer cells). Through a process called Steglish esterification, the initial cholesterol and ergosterol are converted into their respective aldehyde derivatives, by reacting with amines such as 2-amino 6-fluoro benzothiazole, carbohydrazide, and thiosemicarbazide, these aldehyde derivatives are transformed into the appropriate Schiff base derivatives, and then their anticancer activity is checked using the MTT (Microculture Tetrazolium Assay) assay method. For the purpose of analyzing their cytotoxic effects, these compounds were tested on cancerous (SK-GT-4, human esophageal adenocarcinoma) and normal (normal cell line, Rat Embryonic fibroblast (REF)) cell lines. The MTT assay results revealed that the compounds (a1, a2, c1, c2, compound 1) were more harmful to human esophageal cancer cell line than to healthy cell line other than compounds (t1, t2, compound 2, ergosterol and cholesterol alone). Overall, our research indicated that provitamin D2 (ergosterol), a1, a2, c2, t2, compound 1, had a growth-inhibiting effect on both cell lines compared to c1, t1, compound 2, and cholesterol alone.